2007
DOI: 10.1196/annals.1396.046
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Polyunsaturated Fatty Acids and Age‐Related Membrane Changes in the Heart

Abstract: Age-associated modification of cardiac membrane composition and related metabolic processes are major factors underlying the reduced capacity for invoking intrinsic cardioprotective survival mechanisms. In this brief review we examine some of these key membrane lipid modifications, which include alterations in the type and proportion of long-carbon chain polyunsaturated fatty acids (PUFAs). These changes have profound consequences on the efficacy of membrane proteins and lipids involved with numerous processes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
(126 reference statements)
0
11
0
Order By: Relevance
“…Since fatty acids modulate membrane organization and functions (Yehuda et al, 2002; Stillwell et al, 2005; Shaikh and Edidin, 2006; Pepe, 2007; Shaikh and Edidin, 2008), they may affect APP processing. Therefore, we tested the hypothesis that the effects of fatty acids on membrane fluidity and sAPP α secretion depend on the number of double bonds (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Since fatty acids modulate membrane organization and functions (Yehuda et al, 2002; Stillwell et al, 2005; Shaikh and Edidin, 2006; Pepe, 2007; Shaikh and Edidin, 2008), they may affect APP processing. Therefore, we tested the hypothesis that the effects of fatty acids on membrane fluidity and sAPP α secretion depend on the number of double bonds (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species specifically target the GGG triplets in telomeric DNA and result in increased telomere attrition during mitosis 46. Marine omega-3 fatty acids are incorporated into membrane phospholipids, as is arachidonic acid 47. Although EPA and DHA are more readily oxidized ex vivo than arachidonic acid, supplementation with omega-3 fatty acids has been associated with lower levels of F2-isoprostanes, an established standard for measurement of systemic oxidative stress, and with higher levels of the antioxidant enzymes catalase and superoxide dismutase 44,48.…”
Section: Commentmentioning
confidence: 99%
“…This occurs at the expense of -3 PUFA membrane content and is associated with perturbation of metabolic, oxidative and ionic homeostasis, particularly with intracellular calcium management. 19,20 Thus treatment with -3 PUFA not surprisingly counters many of these factors in the experimental setting. In support of a link between -3 PUFA diet and AF is a recent population-based cohort study that prospectively examined 4815 elderly adults (≥65 years) for 12 years, and found that dietary intake of -3 PUFA from fish was associated with markedly lower incidence of AF.…”
Section: Atrial Fibrillation -A Complex Membrane Disordermentioning
confidence: 99%
“…[13][14][15][16][17][18] Many of these effectors underlying AF can be targeted by increasing cardiac membrane -3 PUFA. In cardiac membranes there is an age-related increase in -6 PUFA content and thus precursors of eicosanoids, cytokines and other pro-arrhythmic, pro-inflammatory agents (see reviews by Pepe 19,20 ). This occurs at the expense of -3 PUFA membrane content and is associated with perturbation of metabolic, oxidative and ionic homeostasis, particularly with intracellular calcium management.…”
Section: Atrial Fibrillation -A Complex Membrane Disordermentioning
confidence: 99%